Analysis and Design of Accounting Information Systems at Puri Cipta Sentosa Pharmacy with Method RAD (Rapid Application Development) - Famisyar Astrid Rachariah (Lembaga Intelektual Muda (LIM) Maluku, 2022)
The information technology development, which is growing fast, give the opportunities for business holder to implement computer-based information system in order to record company operational activities. The aim is the owner can get information quickly and accurately for decision-making process. Puri Cipta Sentosa pharmacy is one of the pharmacy in Bondowoso that still use manual recording system to record daily operations. Manual recording system has some weakness, in order to solve these problems, it is necessary to design a computer-based information system. RAD (Rapid Application Development), which is made through a model (prototype), is prioritizing accuracy of system. RAD method consists of several steps. They are: identification the problem, problem analysis, system required analysis, and the design prototype. The design of a prototype using Microsoft Visual Basic 6.0. Microsoft Visual Basic 6.0 is a simple technology to create a picture database. The output that will be generated from the computer -based information system is a accounting system that can be used to record company operational activities quickly and accurately